Single Prolonged Stress as a Prospective Model for Posttraumatic Stress Disorder in Females - Nahvi, Roxanna J.; Nwokafor, Chiso; Serova, Lidia I.; Sabban, Esther L. (Frontiers in Behavioral Neuroscience, 2019)
Sex plays an important role in susceptibility to stress triggered disorders. Posttraumatic Stress disorder (PTSD), a debilitating psychiatric disorder developed after exposure to a traumatic event, is two times more prevalent in women than men. However the vast majority of animal models of PTSD, including single prolonged stress (SPS), were performed mostly with males. Here, we evaluated SPS as an appropriate PTSD model for females in terms of anxiety, depressive symptoms and changes in gene expression in the noradrenergic system in the brain. In addition, we examined intranasal neuropeptide Y (NPY) as a possible treatment in females. Female rats were subjected to SPS and given either intranasal NPY or vehicle in two separate experiments. In the first experiment, stressed females were compared to unstressed controls on forced swim test (FST) and for levels of expression of several genes in the locus coeruleus (LC) twelve days after SPS exposure. Using a separate cohort of animals, experiment two examined stressed females and unstressed controls on the elevated plus maze (EPM) and LC gene expression seven days after SPS stressors. SPS led to increased anxiety-like behavior on EPM and depressive-like behavior on FST. Following FST, the rats displayed elevated TH, CRHR1 and Y1R mRNA levels in the LC, consistent with increased activation of the noradrenergic system. The expression level of these mRNAs were unchanged following EPM, except Y1R. Intranasal NPY at the doses shown to be effective in males, did not prevent development of depressive or anxiety-like behavior or molecular changes in the LC. The results indicate that while SPS could be an appropriate PTSD model for females, sex differences, such as response to NPY, are important to consider.